Methods for processing cemented carbide mining inserts
By applying binder drawing agent on the surface of cemented carbide mining blade and performing dry rolling process, the adhesive is redistributed, which solves the problem of insufficient compression stress in cemented carbide mining blades, and improves fatigue resistance and fracture toughness , extends service life.
Patent Information
- Application Number
- CN202180031655.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-14
- Filing Date
- 2021-05-12
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-05-12
AI Technical Summary
It is difficult for existing cemented carbide mining blades to introduce sufficient compression stress after sintering, resulting in insufficient fatigue resistance and fracture toughness, which affects service life.
By applying a binder pulling agent of metal oxide or metal carbonate on the green surface of the carbide mining blade and performing a dry rolling process after sintering, the binder is redistributed to introduce higher levels of compression stress , a binder-rich and binder-liquid zone is formed, thereby optimizing the hardness gradient and compression stress distribution.
It significantly improves the fatigue resistance and fracture toughness of mining blades, extends service life, and avoids damage to the edge of the blade by traditional tumbling processes. It is suitable for asymmetric blades and high carbon content standard carbide powders.
Smart Images

Figure CN115485084B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method of redistributing a binder in a cemented carbide mining insert and then subjecting the cemented carbide mining insert to a surface hardening process at elevated temperature after sintering, a cemented carbide mining insert having compressive strength produced by the method and its use. Background Art
[0002] Cemented carbide has a unique combination of high elastic modulus, high hardness, high compressive strength, high wear resistance and good toughness level. Therefore, cemented carbide is often used in products such as mining tools. Cemented carbide mining blades are usually treated with edge deburring and surface hardening processes such as tumbling and centerless grinding after sintering. The surface hardening process introduces compressive stress into the mining blade. The presence of compressive stress improves the fatigue resistance and fracture toughness of the mining blade. Therefore, the threshold energy required to fracture the mining blade is higher, thereby reducing the possibility of component collapse, cracking and / or rupture. Therefore, it is desirable to increase the level of compressive stress introduced into the mining blade to increase the service life of the blade.
[0003] In order to maximize the performance of cemented carbide mining inserts, it is desirable to combine these properties and different requirements are placed on the material of different parts of the product. For example, in inserts used for rock drilling and mineral cutting, a tougher inner part is desired to minimize the risk of damage and a harder outer part is desired to optimize wear resistance.
[0004] WO 2010 / 056191 discloses a method of forming a cemented carbide body comprising a hard phase and a binder phase, wherein at least a portion of an intermediate surface zone has a lower average binder content than a portion deeper into the body.
[0005] High Energy Tumbling (HET) methods, such as those disclosed in US7258833B2, provide a way of increasing the level of compressive stress introduced, however it is desirable to be able to further improve the process by providing a method capable of introducing even higher levels of compressive stress into mining inserts without damaging them.
[0006] It is an object of the present invention to provide a method for manufacturing cemented carbide inserts having an optimized hardness gradient and a high level of compressive stress, making them longer lasting and having improved operating properties. Another object is that the method can be applied to asymmetric cemented carbide mining inserts and / or starting from standard carbide powders that are in stoichiometric balance with respect to carbon content or have a high carbon content to enhance the binder pulling effect.
[0007] definition
[0008] "Cemented carbide" herein refers to a material comprising at least 50 wt. % WC, optionally other hard components commonly used in the field of cemented carbide production, and a metal binder phase preferably selected from one or more of Fe, Co and Ni.
[0009] The term "bulk" herein refers to the innermost (center) cemented carbide of a rock drill insert and for purposes of this disclosure is the area having the lowest hardness.
[0010] The term "green" refers to a cemented carbide mining insert manufactured by grinding the hard phase components and a binder together and then pressing the ground powder to form a dense cemented carbide mining insert, which has not yet been sintered.
[0011] The term "binder puller" refers to a substance which, when applied to the surface of a cemented carbide mining insert, causes the binder to migrate towards that surface during the sintering step, i.e. the binder is pulled in the direction of the surface to which the "binder puller" has been applied. Binder pullers work by locally consuming carbon, thereby causing the binder to flow from areas with normal carbon levels to local areas where the carbon level has been depleted. Binder pullers may also act as a WC grain growth inhibitor, which also causes the binder to migrate towards the applied surface where the WC grain size is smaller than in the bulk. Summary of the invention
[0012] According to one aspect of the present invention is a method for redistributing a binder phase of a cemented carbide mining insert, the cemented carbide mining insert comprising a WC hard phase component, optionally one or more other hard phase components and a binder, the method comprising the steps of:
[0013] a) Providing green hard alloy mining inserts;
[0014] b) applying at least one binder pulling agent selected from metal oxides or metal carbonates to at least a localized area of the surface of the cemented carbide insert green body;
[0015] c) sintering the cemented carbide mining insert green body to form a sintered cemented carbide insert; and
[0016] d) subjecting the sintered cemented carbide insert to a dry tumbling process at an elevated temperature above 100°C, preferably above 200°C, more preferably between 200°C and 450°C.
[0017] The method enables the binder to be redistributed in a customized and most advantageous manner, thereby providing the best functionality for the cemented carbide mining insert in combination with the higher level of compressive stress introduced in the cemented carbide mining insert. The applied binder puller is a metal compound that forms an oxide that consumes carbon during sintering. The binder puller is selected from metal oxides or metal carbonates and is applied to at least one local area of the surface of the cemented carbide mining insert green body where carbon is locally consumed during sintering, resulting in the formation of a carbon potential. This will promote the migration of the binder phase from an area with a normal or higher carbon level to this local area with a depleted carbon level. If the binder puller compound causes WC grain refinement, it will also cause the binder to migrate to the surface where the compound is added. This will therefore form a binder-rich area on the local area of the cemented carbide mining insert surface. The cemented carbide mining insert surface to which the binder puller is applied is called an "oxide / carbonate doped" surface. It is well known that the binder-rich area and the binder-poor area will be under tensile stress and compressive stress, respectively, after sintering. This would normally be detrimental to the introduction of tensile stresses. However, the inventors have found that after a treatment such as centrifugal tumbling, high levels of compressive stress can be introduced to a depth of at least 1 mm below the tumbled surface to counteract the tensile stresses present. Thus, the benefits of applying the bond pulling agent can be obtained without the detrimental effects of introducing tensile stresses.
[0018] The "at least one local area on the surface of the cemented carbide mining insert green body" may be any location on the surface, such as the tip, bottom or side, depending on where the binder content increase is desired. The binder puller may be applied to more than one local area on the surface of the cemented carbide mining insert, depending on whether the desired effect is to produce a local increase in toughness or wear resistance. Each "local area" may be 0.5%-85%, preferably 3%-75% of the total surface area of the cemented carbide mining insert.
[0019] The sintering temperature is suitably about 1000° C. to about 1700° C., preferably about 1200° C. to about 1600° C., most preferably about 1300° C. to about 1550° C. The sintering time is suitably about 15 minutes to about 5 hours, preferably about 30 minutes to about 2 hours.
[0020] Higher levels of compressive stress combined with reduced impact defects will improve the fatigue resistance and fracture toughness of the mining blades, thereby increasing the service life of the blades. Other advantages of this approach are that blade geometries, such as blades with sharp bottom radii, which were previously prone to excessive damage to the corners and therefore had low yields, can now be tumbled without causing edge damage. This opens up the possibility of developing mining blade products with different geometries that were not previously suitable for tumbling. Increasing the surface treatment process temperature from room temperature to temperatures such as ~300°C results in improved performance properties of the blade, such as increased crush strength. Cemented carbide toughness increases with temperature, so tumbling at elevated temperatures and impact will not result in defects such as micro cracks, macro cracks or edge chipping.
[0021] The cemented carbide responds better to a surface hardening process at elevated temperatures if there is more binder in the cemented carbide surface zone and / or if the chromium concentration in said surface zone is higher, thereby increasing the strength and toughness of the cemented carbide.
[0022] Another aspect of the present application relates to a cemented carbide mining insert comprising one or more hard phase components and a binder, characterized in that the ratio of % fcc phase Co to % hcp phase Co in the upper half of the insert is >2, preferably >3, more preferably >4.
[0023] The hcp structure is more densely packed than the fcc structure and is a stable structure for pure Co. Co in the hcp phase easily forms twins, which gives it more mechanisms to absorb dislocations without disturbing the lattice. Tumbling at elevated temperatures stabilizes the fcc phase and simultaneously achieves high compressive strength, so more phase changes can occur during drilling, increasing the life of the insert. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 : Graph of crush energy.
[0025] Figure 2 : Hardness distribution of runs 11 (comparative) and 12 (invention).
[0026] Figure 3 : Hardness distribution of runs 4 (comparative) and 14 (invention).
[0027] Figure 4 : Cobalt concentration distribution diagram.
[0028] Figure 5 : Chromium concentration distribution diagram.
[0029] Figure 6 : Cr / Co concentration ratio diagram. DETAILED DESCRIPTION
[0030] In one embodiment of the method, the cemented carbide mining insert contains a hard phase comprising at least 80 wt. %, preferably at least 90 wt. % WC.
[0031] The metal binder of the cemented carbide may contain other elements which dissolve in the metal binder during sintering, such as W and C from WC. Still other elements may dissolve in the binder, depending on what other types of hard components are present.
[0032] In one embodiment, the cemented carbide comprises a hard component in a metal binder phase, wherein the content of the metal binder phase in the cemented carbide is 4 to 30 wt %, preferably 5 to 15 wt %.
[0033] The binder phase content needs to be high enough to provide the toughness behavior of the mining blade. The metal binder phase content is preferably not higher than 30 wt%, preferably not higher than 15 wt%. Too high a binder phase content will reduce the hardness and wear resistance of the mining blade. The metal binder phase content is preferably greater than 4 wt%, more preferably greater than 6 wt%.
[0034] In one embodiment, the metallic binder phase comprises at least 80 wt % of one or more metallic elements selected from Co, Ni and Fe.
[0035] Preferably Co and / or Ni, most preferably Co, even more preferably between 3 and 20 wt% Co. Optionally, the binder is a nickel-chromium alloy or a nickel-aluminium alloy. The cemented carbide mining insert may also optionally contain a grain refining compound, the amount of the grain refining compound being ≤ 20 wt% of the binder content. The grain refining compound is suitably selected from the group of carbides, mixed carbides, carbonitrides or nitrides of vanadium, chromium, tantalum and niobium. The remainder of the cemented carbide mining insert is composed of the one or more hard phase components.
[0036] The one or more other hard phase components may be selected from TaC, TiC, TiN, TiCN, NbC, CrC. The binder phase may be selected from Co, Ni, Fe or mixtures thereof, preferably Co and / or Ni, most preferably Co. The cemented carbide mining insert has a suitable binder content of about 4 to about 3 wt%, preferably about 5 to about 15 wt%. The cemented carbide mining insert may also optionally contain a grain refining compound, the amount of the grain refining compound being ≤ 20 wt% of the binder content. The grain refining compound is suitably selected from the group of carbides, mixed carbides, carbonitrides or nitrides of vanadium, chromium, tantalum and niobium. The remainder of the cemented carbide mining insert consists of the one or more hard phase components.
[0037] In one embodiment of the method, the binder puller, which is a metal oxide or a metal carbonate, is selected from Cr2O3, MnO, MnO2, MoO2, Fe oxides, NiO, NbO2, V2O3, MnCO3, FeCO3, CoCO3, NiCO3, CuCO3 or Ag2CO3. Alternatively, a metal may be applied to the surface of the green hard alloy mining blade, which will form an oxide when heated during the sintering step. The choice of the metal oxide or metal carbonate will affect the properties of the hard alloy after sintering, such as strain hardening, heat resistance and / or corrosion resistance, and a choice can be made that is most suitable for the desired application. If the equivalent metal oxide is toxic while the metal carbonate is not, the metal carbonate will be chosen. In this method, there is a high degree of freedom regarding the location where the binder puller is applied. For example, depending on whether the metal in the oxide or carbonate improves the wear resistance of the hard alloy, the binder puller may be applied in the wear zone of the hard alloy tool or away from the wear zone.
[0038] In one embodiment of the method, the binder puller is Cr2O3. The advantage of using Cr2O3 as the binder puller is that a surface layer of a chromium-rich alloy is formed, enhancing the response to the tumbling treatment. Consequently, higher compressive stresses will be introduced, which will improve the wear resistance of the hard alloy mining blade. Cr2O3 contributes to grain refinement, and thus, a reduced grain size is measured on the side of the blade to which Cr2O3 has been applied.
[0039] The metal oxide or metal carbonate is suitably provided in an amount of from about 0.1 to about 100 mg / cm 2 and preferably in an amount of from about 1 to about 50 mg / cm 2 to one or more surfaces. The starting hard alloy powder blend should suitably have a carbon balance equivalent to 0.75 < Com / %Co < 1, or have an excess of carbon that will compensate for the carbon reduction due to the application of the oxide or carbonate. Com(%) is equal to 100 * 4πσ1 / 4πσ0, where 4πσ1 [μTm 3 / kg] is the weight specific magnetic saturation of the hard alloy blade, and 4πσ0 = 201.9 [μTm 3 / kg] is the weight specific magnetic saturation of pure Co. Com is measured in a Foerster Koerzimat CS.1097 device.
[0040] In one embodiment of the method, the binder puller is applied to the top of the cemented carbide mining blade. In another embodiment of the method, the binder puller is applied to the side of the cemented carbide mining blade. Thus, the properties of the cemented carbide mining blade can be tailored to suit the application. The binder puller may be selectively applied to the location on the surface of the cemented carbide mining blade that is exposed to the highest wear.
[0041] In one embodiment, the method of applying the binder puller is selected from pressing, dipping, painting, spraying (air brushing), stamping or 3D printing. Dipping can be performed with or without a mask. The binder puller can be applied to the surface of the cemented carbide mining blade green body in the form of a liquid dispersion or slurry. In such a case, the liquid phase is suitably water, an alcohol or a polymer such as polyethylene glycol. The concentration of the slurry is suitable for 5-50% by weight of the powder in the liquid phase, for example 10-40% by weight. This range is conducive to achieving the full effect of the binder puller. If the powder content is too high, there may be problems of clogging and agglomeration in the liquid dispersion or slurry. Alternatively, they can be introduced as a solid substance, for example by adding the powder to a suitable position in the pressing mold. The powder can be mixed with a hard phase powder, such as a WC-based powder. The binder puller can also be applied to the cemented carbide mining blade in any other suitable manner. The composition and concentration of the slurry and the way it is applied affect the control of the binder redistribution, thereby enabling the hardness distribution of the cemented carbide mining blade to be controlled.
[0042] Since there is flexibility in where the bond puller is applied, this enables the location of the "wear zone", i.e. where on the surface the combined enhancement of strength and wear resistance is greatest, to be tailored. For example, the wear zone may be located on the top or side of the insert, depending on where the interaction between the cemented carbide mining insert and the rock being drilled is highest. This will vary depending on the application being used and the location of the cemented carbide mining insert on the rock drill bit. Furthermore, since Cr alloying improves wear resistance, the doping may be applied to the largest areas of the insert that are most exposed to the rock during drilling.
[0043] Carbide mining inserts are subject to high compressive loads. Therefore, surface cracking, caused by small cracks growing to a critical size through repeated intermittent high loads, is a common cause of insert failure. It is known that introducing compressive stress into the surface of the insert can reduce this problem, because the presence of compressive stress can prevent crack propagation and wear of the material. Known methods of introducing compressive stress into the surface of cemented carbide mining inserts include shot peening, vibratory tumbling and centrifugal tumbling. These methods are based on mechanical impact or deformation of the outer surface of the body and will increase the service life of the cemented carbide mining insert.
[0044] Case hardening is defined as any treatment that introduces compressive stresses into the material by physical impact, resulting in deformation hardening at and below the surface, such as tumbling or shot peening. The case hardening is performed after sintering and grinding. Surprisingly, it has been found that treating mining blades with a case hardening treatment at elevated temperatures reduces or even eliminates carbide to carbide impact damage in terms of chipping and micro-fracture damage, thereby improving product service life. The case hardening process of the present invention is carried out at an elevated temperature, and this temperature is defined herein as the temperature of the mining blade at the beginning of the case hardening process. The upper temperature limit of the location where the case hardening process is performed is preferably below the sintering temperature, more preferably below 900°C. The temperature of the mining blade is measured by any method suitable for measuring temperature, such as infrared temperature measurement.
[0045] In one embodiment of the invention, the mining blade is surface hardened at a temperature between 100-600°C, preferably between 150-500°C, more preferably at 200-400°C.
[0046] The temperature is measured on the mining blade using any suitable method of measuring temperature. Preferably, an infrared temperature measuring device is used.
[0047] In one embodiment, the method comprises the step of heating the mining blade and media prior to the hardfacing process, and the hardfacing process is performed on the heated mining blade.
[0048] The mining blade may be heated in a separate step prior to the surface hardening process step. A variety of methods may be used to cause the elevated temperature of the mining blade, such as induction heating, friction heating, resistance heating, hot air heating, flame heating, preheating on a hot surface, in an oven or furnace, or using laser heating.
[0049] In an alternative embodiment, the mining blade is kept heated during the hardfacing process, for example using an induction coil.
[0050] The tumbling process can be centrifugal tumbling or vibration tumbling. A "standard" tumbling process will usually be carried out using a vibration tumbling machine, such as Reni Cirillo RC 650, wherein about 30kg of blades will tumble for about 40 minutes at about 50Hz. An alternative typical "standard" tumbling process will use a centrifugal tumbling machine, such as an ERBA-120 with a closed lid on the top and a rotating disc at the bottom. Another method is a centrifugal drum polishing process. In these two centrifugal processes, rotation causes the blade to collide with other blades or with any medium added. For the "standard" tumbling using a centrifugal tumbling machine, the tumbling operation is usually run at least 20 minutes from 120RPM. The lining of the tumbling machine may form oxide or metal deposits on the surface of the blade.
[0051] It may be necessary to modify the lining of the tumbler to enable it to withstand the higher "elevated temperatures" at which the process is carried out.
[0052] In order to introduce higher levels of compressive stress into the cemented carbide mining insert, a high energy tumbling process may be used. There are many different possible process settings that may be used to introduce HET, including the type of tumbler, the volume of media added (if any), the processing time, and process settings, such as the RPM of the centrifugal tumbler, etc. Therefore, the most appropriate way to define HET is in terms of "any process setting that introduces a certain degree of strain hardening in a homogeneous cemented carbide mining insert composed of WC-Co having a mass of about 20 g". In the present disclosure, HET is defined as a tumbling process that introduces at least the following hardness change (ΔHV3%) after tumbling as measured using HV3:
[0053] ΔHV3% = 9.72 - 0.00543*HV3 本体 (Formula 1)
[0054] in
[0055] ΔHV3%=100*(HV3 0.3mm – HV3 本体 ) / HV3 本体 (Formula 2)
[0056] HV3 本体 HV3 is the average value of at least 30 indentation points measured at the innermost (center) of the cemented carbide mining insert. 0.3mmis the average of at least 30 indentation points at 0.3 mm below the tumbled surface of the cemented carbide mining insert. This is based on measurements made on a cemented carbide mining insert with homogeneous properties. By "homogeneous properties" we mean that the hardness difference from the surface area to the body area after sintering does not exceed 1%. The tumble parameters used to achieve the strain hardening described in equations (1) and (2) on a homogeneous cemented carbide mining insert will be applied to a cemented carbide body with gradient properties.
[0057] HET tumbling can typically be performed using an ERBA 120 with a disc size of approximately 600 mm, running at approximately 150 RPM if the tumbling operation is performed without media or with media that is larger than the blade being tumbled, or approximately 200 RPM if the media used is smaller than the blade being tumbled; using an ERBA 120 with a disc size of approximately 350 mm, running at approximately 150 RPM if the tumbling operation is performed without media or with media that is larger than the blade being tumbled, or approximately 200 RPM if the media used is smaller than the blade being tumbled; The tumbler is run at about 200 RPM if the tumbling operation is performed without media or with media that is larger than the tumbled blade, or at about 280 RPM if the media used is smaller than the tumbled blade. Typically, the parts are tumbled for at least 40-60 minutes.
[0058] The effect of surface hardening at elevated temperatures is enhanced if the process is performed under dry conditions. "Dry" conditions refer to no liquid added to the process. Without being found by this theory, it is believed that if a liquid is introduced into the process, it will keep the parts at room temperature. In addition, the inclusion of liquid will reduce the degree of impact between the tumbling parts. The liquid prevents internal friction and collision heat that increase the temperature of the collision point. If no liquid is used, the temperature at the collision point becomes higher, resulting in higher toughness of the material at the collision point.
[0059] Alternatively, the tumbling machine may be pressurized to a pressure that prevents the water from boiling, thereby allowing high temperature tumbling under wet conditions.
[0060] Depending on the geometry and material composition of the mining blade being tumbled, the tumbling process may be performed with or without tumbling media. If a decision is made to add tumbling media, the type of media and ratio to the blade is selected to suit the geometry and material composition of the mining blade being tumbled.
[0061] Optionally, all or part of the heat is generated by friction between the blades and any media added during the tumbling process.
[0062] Optionally, the insert is further subjected to a second surface hardening process. Preferably, if a second surface hardening process performed at room temperature is completed, it is preferred that the second surface hardening process is HET tumbling at room temperature and wet conditions.
[0063] Another aspect of the present invention relates to a cemented carbide mining insert comprising more than one hard phase component and a binder, characterized in that the ratio of % fcc phase Co to % hcp phase Co in the upper half of the insert is >2, preferably >3, more preferably >4. "% fcc Co" is the percentage of Co in the face-centered cubic phase, and "% hcp Co" is the percentage of Co in the hexagonal close-packed phase. The percentages of each phase can be measured using EBSD. An increase in the ratio of % fcc phase Co to % hcp phase Co in the upper half of the insert results in an insert with higher crushing strength. For pure Co, hep is the stable phase and fcc is metastable. Most commonly, the dominant phase in cemented carbide is fcc due to alloying of carbon and tungsten during sintering. The surface hardening treatment induces defects in the binder, namely stacking faults and dislocations. When the tendency to form stacking faults increases, it improves the mechanical properties of fcc Co. As the strain increases, the mobility of defects will be restricted and a phase transformation from fcc to hcp will occur in the material. By being able to stabilise the fcc Co phase, this means that more fcc to hcp conversion will occur during drilling. Therefore, starting materials with a higher fcc to hcpCo ratio are favoured.
[0064] Surface doping causes Co to migrate to the doped area during sintering, in this case the top of the drill insert. The alloying effect of Cr and the grain growth inhibition effect brought by Cr should also affect the magnetic coercivity and magnetic ratio. Therefore, there is a difference in magnetic properties between the top and bottom.
[0065] In one embodiment:
[0066]
[0067] Among themCom T is the percentage of magnetism in the upper half of the blade, Com B It is the percentage of magnetism in the lower half of the blade. T is the magnetic coercivity of the upper half of the blade, Hc B is the magnetic coercivity of the lower half of the blade. Hc and Com are the magnetic coercivity and magnetic percentage of the blade before cutting.
[0068] In one embodiment, %Cr T is the weight percentage of Cr in the upper half of the insert, %Cr B Is the weight percentage of Cr in the lower half of the insert. Higher levels of chromium in the tip of the insert will result in increased wear resistance, which will result in improved drilling performance.
[0069] In one embodiment, the hardness measured 150 μm below the surface is at least 20 HV3, preferably at least 30 HV3 higher than the hardness measured in the body. This hardness profile is most ideal for rock drill inserts as it provides a hard surface and a tough body.
[0070] The hardness of the cemented carbide insert is measured using the Vickers hardness automatic measurement. The cemented carbide body is cut along the longitudinal axis and polished using a standard procedure. The cutting is completed under flowing water with a diamond disc cutter. The Vickers indentation under a load of 3kg is then distributed on the polished section at a given depth below the surface. The hardness of the top surface area is the average value of about 20 indentations (non-doped inserts) or 30 indentations (doped inserts) made at a given distance of 150 μm below the surface below the dome. The hardness of the bottom surface area is the average value of about 18 indentations (non-doped inserts) or 24 indentations (doped inserts) made at a given distance of 150 μm below the surface below the bottom.
[0071] The hardness measurements were performed using a programmable hardness tester KB30S from KB Prüftechnik, which was calibrated against a HV1 test block issued by the Euro Products Calibration Laboratory, UK. The hardness was measured in accordance with ISO EN6507-01.
[0072] HV3 measurements are performed as follows:
[0073] -Scan the edge of the sample.
[0074] - The hardness tester is programmed to make an indentation at a specified distance from the edge of the sample.
[0075] - Indentation with 3kg load at all programmed coordinates.
[0076] -The computer moves the stage to each coordinate, positions the microscope on each indentation, and runs automatic light adjustment, automatic focus, and automatically measures the size of each indentation.
[0077] -User checks all embossed photos for focus and other things that interfere with the results.
[0078] In one embodiment, there is a first binder concentration minimum (%binder-min) between the doped surface and the body, which is between 1%-50%, preferably between 5%-40% from the doped surface as a percentage of the total height of the sintered cemented carbide mining insert. The %binder-min is typically at a depth of 0.5-10 mm, preferably 0.8-7 mm, from the first portion of the surface.
[0079] In one embodiment, there is a first chromium concentration maximum at the doped surface.
[0080] In one embodiment, the cobalt concentration is higher in the upper half of the mining blade compared to the lower half of the mining blade.
[0081] In one embodiment, the chromium concentration is higher in the upper half of the mining blade compared to the lower half of the mining blade.
[0082] The chemical concentration within the cemented carbide mining insert was measured along the cross-sectional centerline of the cemented carbide mining insert using wavelength dispersive spectroscopy (WDS).
[0083] In one embodiment, the mining blade is uncoated.
[0084] Another aspect of the present disclosure relates to the use of a cemented carbide mining insert as described above or below in rock drilling or oil and gas drilling.
[0085] Example
[0086] Example 1 - Starting Materials and Tumbling Conditions
[0087] Experimental design (DOE) is used to plan experiments where input factors are varied in a systematic way in the factor space to understand the response of the process under study. In this case, JMP software from SAS was used. The user design option in the software was selected to vary the factors of binder concentration, carbon balance, doping level and tumbling temperature. The magnetic coercivity (kA / m) and cobalt magnetic proportion (Com%) were measured after sintering and grinding and again after tumbling.
[0088] A summary of the composition, dopants and tumbling temperatures of the tested mining inserts, as well as the measured magnetic properties, are shown in Table 1. Com did not change significantly during tumbling.
[0089]
[0090] Table 1: Composition of the tested mining inserts. * Balance is WC.
[0091] All cemented carbide inserts were made using WC powders with a particle size between 5 and 18 μm measured by FSSS before grinding. WC and Co powders were ground in a ball mill under wet conditions using ethanol and adding 2 wt% of polyethylene glycol (PEG 8000) as an organic binder (pressing agent) and cemented carbide grinding bodies. After grinding, the mixture was spray dried in a N2 atmosphere and then uniaxially pressed into GT7S100A mining inserts with an outer diameter (OD) size of about 10 mm, a height of about 16-20 mm and a weight of about 17 g, each with a spherical dome ("cutting edge") on top. The inserts were doped by vertically dipping the tip of the insert downward into a slurry containing Cr2O3 and PEG300 to a depth corresponding to half of the cylindrical portion of the insert or about 11 mm of the total insert height. Three different Cr2O3 concentrations were used, 15%, 20% and 26%, see Table 1. 15% Cr2O3 suspension resulted in 8-10 mg Cr2O3 per blade, 20% Cr2O3 suspension resulted in 15-16 mg Cr2O3 per blade, 26% Cr2O3 suspension resulted in 17.5-20 mg Cr2O3 per blade. The samples were then sintered using Sinter-HIP at 55 bar Ar pressure and 1410°C for 1 hour and then ground.
[0092] After sintering and polishing, in order to replicate tumbling at elevated temperatures on a laboratory scale, a "hot shaking" method was used. The hot shaking method used the trademark Corob TMA commercially available paint shaker of Simple Shake 90, with a maximum load of 40 kg and a maximum shaking frequency of 65 Hz. The "hot shake" method is performed at a frequency of 45 Hz. About 800 grams or 50 blades and 4.2 kg of carbide media (1560 balls of about 7 mm) are placed in a cylindrical steel container with an inner diameter of 10 cm and an inner height of 12 cm, filled to 2 / 3 of the height. The steel cylinder with the mining blades is heated in a furnace with the media to an elevated temperature of 150°C or 300°C, and the mining blades are kept at this target temperature for 120 minutes. After heating, the steel cylinder is immediately transferred to a paint shaker and immediately shaken for 9 minutes. The transfer time between the furnace and the start of the shaker is less than 20 seconds. The media is made of H10F grade cemented carbide with 10 wt% Co, 0.5 wt% Cr and 89.5 wt% WC, resulting in a sintered HV20 of about 1600. The shaking was carried out under dry conditions, i.e. no water was added during the shaking at 150°C or 300°C. Temperature measurements were made using a laser-guided infrared thermometer M7 from MIKRON and the temperature on the blade inside the container was taken. To prevent temperature increases in runs 1-6 carried out at 25°C, a 100 ml amount of water was added to the batch of blades and medium. For all runs, the blades were left to cool to room temperature and then A final wet centrifugal tumbling operation was performed at 300 RPM for 50 minutes in a FKS04 tumbling machine with 50 kg of 7 mm H10F tumbling media (the post-tumbling Hc measurements in Table 1 are after these two tumbling steps).
[0093] Example 2 - Edge Damage
[0094] For maximum productivity, it is important that damage to the edge of the mining blade after tumbling is low, preferably completely absent. The area most susceptible to chipping is at the sharp corner between the bottom and side of the blade, where the radius is typically about 0.5 mm.
[0095] Visual inspection of the mining blades for damage after tumbling showed that the surfaces of samples hardened at either 150°C or 300°C did not show any edge damage, even at the sharpest radius between the base and side of the blade.
[0096] Example 3 - Blade Compression Test
[0097] The blade compression test method involves compressing the drill bit blade between two parallel hard counter surfaces at a constant displacement rate until the blade fails. A test fixture based on the ISO 4506:2017 (E) standard "Hardmetals-Compression test" is used, with carbide anvils with a hardness of more than 2000 HV, while the test method itself is adapted to the toughness test of rock drill blades. The fixture is mounted on an Instron 5989 test frame.
[0098] The loading axis is the same as the axis of rotational symmetry of the blade. The opposing surfaces of the fixture meet the parallelism required in the ISO 4506:2017 (E) standard, i.e., the maximum deviation is 0.5 μm / mm. The blade under test is loaded at a constant crosshead displacement rate equal to 0.6 mm / minute until damage, and the load-displacement curve is recorded. Before the test evaluation, the compliance of the test equipment (rig) and the test fixture is subtracted from the measured load-displacement curve. For each run, five blades were tested. Check the damage of the opposing surfaces before each test. When the measured load suddenly drops by at least 1000N, it is defined as blade damage. Subsequent inspection of the blade under test confirmed that in all cases, this is consistent with the occurrence of macroscopic visible cracks. Material strength is characterized by the total absorbed deformation energy until rupture. The total fracture energy (Ec) required to crush the sample is shown in Joules (J) as shown in Table 2 below:
[0099] run Fracture energy Ec(J) 1 9.3 2 9.3 3 10.9 4 9.4 5 9.0 6 10.2 7 11.0 8 10.1 9 10.4 10 9.9 11 10.5 12 11.3 13 10.8 14 10.0 15 10.9 16 10.3
[0100] Table 2: Fracture energy required to crush the samples (J)
[0101] Figure 1 The following is a graph modeled from the DOE results Tables 1 and 2 showing the effect of tumbling temperature and Cr2O3 concentration in the dopant on the crushing strength of a 6% Co grade with Com / Co = 0.9 and a bulk hardness of 1400 HV3. Figure 1 As can be seen in the graph, the crush strength increases with increasing tumbling temperature and the amount (concentration) of Cr2O3 slurry used for doping. The combination of increased wear resistance and increased crush strength due to Cr in the binder improves blade performance.
[0102] Example 4 - Hardness Measurement
[0103] The hardness of the cemented carbide insert is measured using the automatic Vickers hardness measurement as described above. The cemented carbide body is sectioned along the longitudinal axis and polished using a standard procedure. The sectioning is completed under flowing water with a diamond disc cutter. The Vickers indentation under a load of 3kg is then distributed on the polished cut surface at a given depth below the surface. In the case of non-doped operation, the distance between the indentations is 0.7mm at a depth of 0.15 and 0.3mm, 0.6mm at a depth of 0.6 and 1.2mm, and 0.4mm at a depth of 2.4 and 4.8mm. For doped operation, the distance between the indentations is 0.5mm at a depth of 0.15, 0.3, 0.8, 1.3, 1.8, 2.3, 2.8, 3.3, 3.8, 4.3 and 4.8mm.
[0104] The hardness of the top surface zone is the average of about 20 indentations for non-doped inserts or about 30 indentations for doped inserts made under the dome at a given distance of 150 μm below the surface. The hardness of the bottom surface zone is the average of about 18 indentations for non-doped inserts or about 24 indentations for doped inserts made under the bottom at a given distance of 150 μm below the surface.
[0105] The bulk hardness is the average of about 30 indentations for non-doped inserts or about 60 indentations for doped inserts, and the bulk hardness measurement is made at the innermost distance. For each run, two samples were measured. Table 3 shows a summary of the hardness measurements after tumbling.
[0106]
[0107] Table 3: Hardness measurement
[0108] Figure 2 is the hardness distribution from the tip to the bottom of the blades of Run 11 (Comparison) and 12 (Invention), Figure 3 is the hardness profile of the inserts for Runs 4 (comparative) and 14 (inventive). The profiles show that the hardness is higher at the surface than in the bulk, and that the tumbling increases the hardness at the base and tip by about the same amount when looking at undoped Runs 4 and 11.
[0109] Example 5 - Chemical Analysis
[0110] The chemical gradient of the samples was investigated by wavelength dispersive spectroscopy (WDS) analysis using a Jeol JXA-8530F microprobe. Line scans along the centerline of the cross-section of the sintered material were performed, followed by tumbling of a carbide insert containing 6 wt% Co and 96 wt% WC and a carbide insert containing 11 wt% Co and 89 wt% Co, the surfaces of which were domed (equivalent to a concentration of 0.25-0.28 mg / mm) by immersing the sample in a slurry containing 30 wt% Cr3O2 and 70 wt% PEG300. 2 ) was doped in such a way that approximately 60% of the total blade length was exposed to the oxide slurry. The samples were prepared using precision tools and then mechanically ground and polished. The final step in sample preparation was polishing with 1 μm diamond paste on a soft cloth. Line scans were performed using an accelerating voltage of 15 kV, a step size of 100 μm, and a probe diameter of 100 μm. Three line scans were performed for each sample and the average value was reported. Figure 4 shows the chemical distribution of cobalt concentration, Figure 5 shows the chemical distribution of chromium concentration, Figure 6 The Cr / Co chemical distribution of the 6 wt% and 11 wt% Co samples before tumbling is shown. The tumbling treatment does not affect the chemical composition, so the same chemical gradient distribution will be present after tumbling.
[0111] Chromium concentrations in the upper and lower halves of the inserts were measured using X-ray fluorescence (XRF) according to ASTM B 890-07 using a Malvern Panalytical Axios Max Advanced instrument. For chromium measurements, one insert per run was cut orthogonally into upper and lower halves using a 1 mm diamond disc cutter, with each section having approximately the same height (± 0.5 mm).
[0112] Then for the chromium doped insert, we express the chromium ratio as:
[0113] %Cr T is the percentage of Cr in the upper half of the insert, %Cr B is the percentage of Cr in the lower half of the insert.
[0114]
[0115] Table 4: Chromium concentration measurements
[0116] Example 6 - Magnetic Properties
[0117] The magnetic coercivity (Hc) and magnetic percentage ratio Com (%) were measured after tumbling. The three blades of each run were then orthogonally cut into upper and lower halves using a 1 mm diamond disc cutter, each having approximately the same height (± 0.5 mm). Hc and Com were measured again for each half. Hc T and Hc B The measured magnetic coercivity of the upper and lower halves of the blade, respectively. T and Com B The measured magnetic percentage ratios are the upper and lower halves, respectively. These measurements are recorded in the table below together with α, which is calculated by the following formula:
[0118]
[0119]
[0120] Table 5: Magnetic measurements after tumbling
[0121] Example 7 - Electron Backscatter Diffraction (EBSD)
[0122] EBSD measurements are performed on the samples to generate microstructural maps of the samples at selected locations. These maps are evaluated using crystallographic information to determine the phase.
[0123] The measurements were taken at a depth of 0.5 mm from the surface to represent the microstructure of the top of the blade, and at 10 mm from the blade surface to represent the microstructure of the blade body. The blades for EBSD were prepared by mechanical polishing of the plane parallel cross section using 9 μm diamond slurry down to a diamond size of 1 μm, followed by an ion polishing step in flat mode in a Hitachi IM 400. The prepared sample was then mounted on a sample holder and inserted into a scanning electron microscope (SEM). The sample was tilted 70 degrees relative to the horizontal plane and toward the EBSD detector. The SEM used for characterization was a Jeol JSM-7800F, using a 70 μm IM objective aperture. The EBSD detector used was an Oxford Instruments nordys detector, operated using Oxford Instruments' "AZtec" software version 4.3. EBSD data acquisition was performed by applying a focused electron beam to the polished surface and sequentially acquiring EBSD data for a 90 μm × 90 μm area using a step size of 0.05 μm. The SEM settings used were: accelerating voltage = 20 kV; aperture = 70 μm; working distance = 15 mm; detector insertion distance = 182 mm; optimization mode: binning 4×4; static background on, automatic background on; optimization solver: optimize TKL model; number of bands 8; Hough resolution 60; apply refinement on. The reference phases used were:
[0124] WC (hexagonal phase), 41 reflectors, Acta Ctystallogr., [ACCRA9], (1961), Vol. 14, pp. 200-201.
[0125] Co (cubic phase), 44 reflection planes, Journal of Applied Physics (Z.Angew.Phys.), [ZAPHAX], (1967), Vol. 23, pp. 245-249. Co (hexagonal phase), 44 reflection planes, Physics of Metals and Metallography (Fiz.Met.Metalloved), {FMMTAKJ, (1968), Vol. 26, pp. 140-143.
[0126] EBSD data were collected and analyzed in AZtec 3.4. Noise reduction was performed by removing wild spikes and performing zero removal with extrapolation level 3 (low level). 2 samples were measured for each run. The following table shows the average ratio of fcc Co vs hcp Co measured in the upper and lower halves of the insert:
[0127]
[0128] Table 6: Average Co phase fraction measured using EBSD
Claims
1. A method for redistributing the binder phase of a cemented carbide mining insert, the cemented carbide mining insert comprising a WC hard phase component, optionally one or more other hard phase components and a binder, the method comprising the following steps: a) Providing green hard alloy mining inserts; b) applying at least one binder pulling agent selected from metal oxides or metal carbonates to at least a localized area of the surface of the cemented carbide mining insert green body, wherein the localized area is 0.5% to 85% of the total surface area of the cemented carbide mining insert; wherein a binder puller is a substance which when applied to the surface of said cemented carbide mining insert causes said binder to migrate to the surface during the sintering step; c) sintering the cemented carbide mining insert green body to form a sintered cemented carbide mining insert; d) heating the cemented carbide mining insert and media prior to a surface hardening process, wherein the cemented carbide mining insert is heated using induction heating, resistance heating, hot air heating, flame heating, preheating on a hot surface, in an oven or furnace, or using laser heating; e) subjecting the sintered cemented carbide mining insert to a dry tumbling process at an elevated temperature above 100°C.
2. The method of claim 1, wherein the bond pulling agent is Cr2O3.
3. The method of claim 1 or 2, wherein the cemented carbide mining insert remains heated during the surface hardening process.
4. The method of claim 1 or 2, wherein part of the heat is generated by friction between the cemented carbide mining insert and any media added during the tumbling process.
5. The method according to claim 1 or 2, wherein the tumbling process is a "high energy tumbling" process, wherein after tumbling, the homogeneous cemented carbide mining insert has been strain hardened to make ΔHV3% ≥ 9.72-0.00543*HV3 本体 , where ΔHV3% is the percentage difference between the HV3 measurement at 0.3 mm from the surface and the HV3 measurement in the body, where hardness is measured according to ISO EN 6507-01.
6. The method of claim 1 or 2, wherein the cemented carbide mining insert is subjected to a second surface hardening process at room temperature after the cemented carbide mining insert has been subjected to the surface hardening process at an elevated temperature.
7. The method of claim 6, wherein the second surface hardening step is high energy tumbling.
